2010
DOI: 10.1111/j.1476-5381.2010.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

α1‐Adrenoceptor‐mediated contraction of rat aorta is partly mediated via transactivation of the epidermal growth factor receptor

Abstract: Background and purpose:High level of plasma catecholamines is a risk factor for vascular diseases such as hypertension and atherosclerosis. Catecholamines induce hypertrophy of vascular smooth muscle through a1-adrenoceptors, which in cell culture involves the transactivation of epidermal growth factor receptor (EGFR). We hypothesized that EGFR transactivation was also involved in contractions of rat aorta mediated by a1-adrenoceptors. Experimental approach: Thoracic aorta was isolated from 12-14 week old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
4
22
0
1
Order By: Relevance
“…Nevertheless, our results are in accordance with previous studies in which ERK inhibition reduced PE-induced contractions in MRAs from diabetic mice (28). However, these results are still not clear since a previous study showed that ERK1/2 inhibition did not affect PE-induced contraction in aorta from rats (47). These results suggest that the role of ERK1/2 in ␣ 1 -adenoreceptor-mediated contraction shows considerable heterogeneity depending on vessel types.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, our results are in accordance with previous studies in which ERK inhibition reduced PE-induced contractions in MRAs from diabetic mice (28). However, these results are still not clear since a previous study showed that ERK1/2 inhibition did not affect PE-induced contraction in aorta from rats (47). These results suggest that the role of ERK1/2 in ␣ 1 -adenoreceptor-mediated contraction shows considerable heterogeneity depending on vessel types.…”
Section: Discussionsupporting
confidence: 81%
“…We recently had demonstrated that a 1 -AR induced transactivation of EGFR contributes to VSMC contraction in rat aorta (i.e., to immediate affect the a 1 -AR response) (Ulu et al, 2010), so we first explored whether a similar transactivation occurs in serum-starved cultured A7R5 VSMCs, which express all three a 1 -ARs (data not shown). Stimulation of a 1 -AR by 10 mM PE and EGFR by 1 nM EGF induced phosphorylation of EGFR in A7R5 VSMCs.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, a 1 -AR stimulation resulted in EGFR phosphorylation in rat aorta, while the EGFR kinase inhibitors AG1478 [4-(39-chloroanilino)-6,7-dimethoxyquinazoline] and DAPH (4,5-dianilinophthalimide) concentration-dependently attenuated phenylephrine (PE)-induced contractile responses (Ulu et al, 2010). Moreover, in our recent study, EGFR kinase inhibitor …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in heart failure, increased myogenic constriction of mesenteric artery is due to AT 1 R-mediated transactivation of EGFR (Xu et al, 2009). Moreover, we recently showed that transactivation of the EGFR governs part of the a 1 -AR-induced contraction of rat aorta (Ulu et al, 2010). A potential mechanism involved in EGFR transactivation is GPCRinduced shedding of heparin-binding EGF-like growth factor, which subsequently activates EGFR (Asakura et al, 2002).…”
Section: Introductionmentioning
confidence: 99%